PELAKSANAAN PENEGAKAN HUKUM TINDAK PIDANA DI BIDANG PERIKANAN BERDASARKAN UNDANG-UNDANG NOMOR 45 TAHUN 2009 TENTANG PERIKANAN DI KEPOLISIAN RESOR ROKAN HILIR - Laksamana, Arief; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Rokan Hilir waters renowned for its marine resources , especially fisheries results . It causes a lot of Indonesian fishermen and foreign fishermen who catch fish in these waters by illegal means . Law enforcement against criminal acts fisheries ( illegal fishing ) in the waters of Rokan Hilir not been able to come to fruition , due to the constraints faced by law enforcement is well constraints and constraints in the field of technical and non- technical . The purpose of this study , to investigate the implementation of law enforcement against criminal acts Fisheries by Act No. 45 of 2009 on Fisheries in Rokan Hilir Police , to determine obstacles in the implementation of law enforcement against criminal acts Fishing in Police Rokan Hilir , to know the effort made in overcoming obstacles to the implementation of law enforcement in criminal acts Fisheries Police Rokan Hilir .The research was conducted by means of sociological research . Data used in this research is to use primary data ( data obtained directly from the respondents of the interviews . The primary data is in the form of data on the root causes of crime in the area Fishing in the jurisdiction of Police Rokan Hilir ) , secondary data ( data obtained by researchers from various studies literature and legislation , literature books and expert opinions related to this research problem ) , and the data tertiary ( Indonesian dictionary ) , data collection techniques in this study through : interview ( interview) that is doing engineering interviews with respondents regarding the problems studied , the questionnaire ( questionnaire ) , which is a tool of research or survey consisting of a series of written petanyaan , aims to obtain feedback from respondents selected through questions .Implementation of law enforcement against criminal acts fisheries done by preventive and repressive . But in reality the rule of law in the field of fisheries has not received a bright spot in revealing any criminal offense fisheries crime ( illegal fishing ) . Suggestions writer , first in combating the crime of fisheries ( illegal fishing ) Police should increase the number of police personnel due to the vast waters cover the district , both in dealing with the development of every crime that happened the police it is essential to add the necessary facilities and infrastructure in law enforcement , law enforcement third criminal offense in Rokan Hilir is a shared responsibility that law